(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article provides information about the Karakol breed of sheep, which is mainly bred to obtain high-quality commercial Karakol skins; the coarse wool obtained from them is a commercial product that ensures a certain economic sustainability of livestock farms. The wool productivity of Karakol sheep is influenced by their live weight, color, gender, level of fatness, type of fat, type of wool constitution and many other factors.